Well Done, Secret Seven - Blyton, Enid (London Hodder Children's Books, 2004)
The Secret Seven have a new meeting place - a treehouse! But someone else is using it too. The gang are furious, but then they learn the intruder is in big trouble and needs their help. Can the Seven come to the rescue ...?
Keywords: Children's Literature - Fiction : Adventure